As representações sociais do cuidado materno ao longo dos séculos - Dias, Lusiene Araújo da Conceição (2024)
This study aims to understand the social representations of maternal care in western society over the centuries, through the sociocultural and historical context projected on women when they become mothers. It also seeks to reflect under what conditions maternal care work was carried out and which bodies were most favorable for carrying out their duties. And observe, through images that represent motherhood and care, the bond established between those who care and those who are cared for, a context discussed in the projections by Élisabeth-Louise Vigée-Le Brun (1789), with the work Self-portrait with daughter Julie; Mary Cassat (1800), with Breastfeeding; Louise Bourgeois (1990), with Maman, and Thais Basilio (2020), with Colo. For this understanding, theories focused on the sexual division of labor, gender, motherhood and care work. It is a bibliographical research, which has as its starting point the understanding of the sociocultural and historical context surrounding maternal care developed in the last four centuries. For data collection, illustrations by women artists were used that portrayed motherhood in their works and contextualized with the temporality of each era. Data analysis focused on content analysis and semiotics in order to make conjectures based on the exercise of care work by means of experience and sociocultural prominence. The results obtained revealed that maternal care work continues to be mostly done by women, racialized and from popular classes, who still work double or triple shifts, elements that favor physical and mental exhaustion.